LE PARC NATIONAL DE LA MARAHOUE : DE LA LOGIQUE DE CONSERVATION A LA LOGIQUE DE PREDATION - Goh Denis (European Scientific Journal, ESJ, 2015)
This study is the result of research on the factors explaining the degradation of Marahoue National Park, in the central west of Côte d’Ivoire. Besides the literature search, the individual and group interviews conducted using interview guide among people of different social categories allowed to collect the required information within the framework of this study. It emerges from the investigations that the current state of the conservation of this park is the result for the combination of several factors: these include inconsistencies decisions of public authorities, permissiveness and corruption of park staff, low consciousness among many population, the need to preserve the park and lack of material resources and human shortage for the conservation of the park. Ultimately, in spite of the assertion of its protected area status by the administrative authorities, Marahoue National Park is in danger, primarily because of the extend of clearing for agriculture and poaching which take place there. The responsibilities in the degradation of this important protected area are extensive, extending from basic population to the authorities via site managers.